The Power of Social Emotional Learning: Building Self Confidence, Emotional Intelligence and Independence in Early Childhood Ages 4-5 in Preschool Abc Jakarta - Diandra Ruth Jayaputra; Sri Lanawati Raharja (Syntax Corporation Indonesia, 2024)
The skills of selfconfidence (SC), emotional intelligence (EI), and independence (IDC) should be trained as early as possible. It is required for early childhood to have a strong foundation for their future. These skills can be learned and trained using the RULER approach with the method of Mood Meter. The purpose of this study is to observe any difference in the levels of these skills after undergoing the Mood Meter. This research is conducted in children aged 4-5 in Preschool ABC Jakarta with 9 participants in total consisting of 6 girls and 3 boys. The methods used in the research are quasi-experimental with one group pre and posttest. A t-test and N-gain were conducted for the hypothesis testing. Results show moderate effectiveness in increasing SC, particularly in areas like perseverance and participation. EI also showed a moderate increase, with students displaying more internal motivation. However, the biggest impact was on IDC, with students demonstrating significantly higher levels of responsibility and personal care. The Mood Meter likely helped students manage their emotions and understand routines, leading to better classroom behaviour and adjustment.